Hubungan Pengetahuan dan Dukungan Keluarga Terhadap Kepatuhan Ibu Hamil Mengkonsumsi Tablet Zat Besi di RSU Tere Margareth Medan Tahun 2023 - Satria Vitria Rajagukguk; Dessy Ratna Sari; Ninsah Mandala Putri Sembiring; Zulkarnain Batubara; Indra Septian Manurung (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The anemia prevention program for pregnant women provides 90 Iron tablets during pregnancy to reduce anemia, but the incidence of anemia is still high. Failure to get iron tablet coverage is due to forgetting, nausea and laziness to take iron tablets. The purpose of the study was to find out the knowledge and support of families towards respect for the consumption of iron tablets by pregnant women in the Tere Margaret Hospital work area in 2023. This study only uses family knowledge and support as independent variables while compliance with iron tablet consumption is the dependent variable. The research design is an analytical investigation with a cross-sectional approach. Data collection using secondary and primary data. The research sample only consisted of pregnant women. pregnant women 28-40 weeks in the Tere Margaret Hospital work area in 2023, with a total of 48 people. pregnant women. the results of the study, especially respondents (54.2%) have less knowledge of iron tablets (Fe), most respondents (68.8%) do not receive support from their families or husbands to consume iron tablets (Fe), there are also respondents (64.6%) are not consistent in consuming iron. The results of the multiple t-test showed that there was a significant relationship between knowledge and family support regarding pregnant women who consume iron tablets in the Tere Margaret Hospital work area in 2023. Health services must increase the dissemination of information through public awareness through the role of leaders in increasing knowledge about the importance of routine consumption of iron tablets for pregnant women every day.